2020
DOI: 10.1111/1462-2920.15020
|View full text |Cite
|
Sign up to set email alerts
|

The novel and transferable erm(51) gene confers macrolides, lincosamides and streptogramins B (MLSB) resistance to clonal Rhodococcus equi in the environment

Abstract: Summary The use of mass antimicrobial treatment has been linked to the emergence of antimicrobial resistance in human and animal pathogens. Using whole‐genome single‐molecule real‐time (SMRT) sequencing, we characterized genomic variability of multidrug‐resistant Rhodococcus equi isolated from soil samples from 100 farms endemic for R. equi infections in Kentucky. We discovered the novel erm(51)‐encoding resistance to MLSB in R. equi isolates from soil of horse‐breeding farms. Erm(51) is inserted in a transpos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…The R. equi colonies from the NANAT agar plates containing erythromycin and/or rifampicin were tested for the presence of the species-specific gene choE [22] and the presence of the virulence gene vapA using conventional PCR as previously developed [14,23]. The presence of macrolide AMRGs was determined by PCR amplification of erm(46) [24] and erm(51) [25] following previously developed protocols [24,25]. R. equi were classified as carrying AMRGs if either or both erm (46) and erm(51) were detected by PCR.…”
Section: Sample Processingmentioning
confidence: 99%
“…The R. equi colonies from the NANAT agar plates containing erythromycin and/or rifampicin were tested for the presence of the species-specific gene choE [22] and the presence of the virulence gene vapA using conventional PCR as previously developed [14,23]. The presence of macrolide AMRGs was determined by PCR amplification of erm(46) [24] and erm(51) [25] following previously developed protocols [24,25]. R. equi were classified as carrying AMRGs if either or both erm (46) and erm(51) were detected by PCR.…”
Section: Sample Processingmentioning
confidence: 99%
“…Among the Erm methyltransferases described to date, the ErmC class is the most prevalent in staphylococci (e.g., Staphylococcus aureus ), while the ErmB and ErmA classes are the most common in enterococci (e.g., Enterococcus faecalis ) and streptococci (e.g., Streptococcus pneumoniae ) [ 192 , 193 , 194 , 195 ]. Erm genes in most microorganisms are located within the transposons and, as a mobile genetic element, they are involved in the spread of the so-called MLSB-type resistance [ 196 , 197 , 198 ]. In linezolid-resistant bacteria, plasmid-encoded methyltransferases, products of the cfr gene, are responsible for the modification of 23S rRNA by adding a methyl group to the C8 atom of its A2503 adenine ( Escherichia coli numbering).…”
Section: Mechanisms Of Antibiotic Resistancementioning
confidence: 99%
“…BLAST+ v2.9.0 [37] was used to align the contigs of 207 R. equi isolates characterized in our earlier studies [32,33,35] to known R. equi genetic elements (R. equi chromosome, pVAPA, pRErm46, and erm(51)) at >95% identity and >80% coverage. Similarly, BLASTn [37] was used to align the unknown contigs from sample 156 to the other novel contigs and the nucleotide NCBI database.…”
Section: Bioinformatic Analysismentioning
confidence: 99%
“…To date, isolates resistant to macrolides and/or rifampin have been reported in 16 US states [24], China [6,27], Ireland [28,29], France [30], and Poland [31]. Our previous work revealed that in the US, R. equi isolates resistant to macrolides and rifampin are mainly clustered in three clonal populations: clone 2287, clone G2016, and clone G2017 [26,32,33]. Clone 2287 harbors pRErm46, a 90 kb conjugative plasmid that carries antimicrobial resistance genes (ARGs) for macrolides, lincosamide, streptogramin B (MLS B ), tetracycline, and sulfamethoxazole [34] and a chromosomal rpoB S531F mutation conferring resistance to rifampin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation